Effect of photoperiod and temperature on the intensity of pupal diapause in the cotton bollworm, Helicoverpa armigera (Lepidoptera: Noctuidae). Issue 1 (February 2014) - Chen, Chao; Xia, Qin-Wen; Fu, Shu; Wu, Xian-Fu; Xue, Fang-Sen
Abstract The intensity of pupal diapause in the cotton bollworm, Helicoverpa armigera (Hübner) was investigated under both laboratory and natural conditions. By transferring diapausing pupae induced under LD 11:13, LD 12:12 and LD 13:11 at 20, 22 and 25 °C to 25 °C combined with LD 15:9 to terminate diapause the rearing day length of 11 h evoked greater intensity of diapause than did 12 and 13 h at 25 °C; whereas the rearing temperature of 25 °C evoked more intense diapause than did 20 and 22 °C under LD 11:13. By transferring diapausing pupae induced under LD 12:12 at 20 and 22 °C to six temperatures of 18, 20, 22, 25, 28 and 31 °C combined with LD 15:9 to terminate diapause, the duration of diapause was significantly shortened from 146 days at 18 °C to 24 days at 31 °C, showing that high temperatures significantly accelerate diapause development. Furthermore, the duration of diapause was significantly longer at the rearing temperature of 22 °C than that at 20 °C when the diapause-terminating temperatures were 20 and 22 °C. Chilling at 5 °C did not shorten the duration of diapause but lengthened it when chilling period was included. However, chilling plays an important role in synchronizing adult emergence. Rearing temperature of 22 °C also evoked more intense diapause than did 20 °C in most chilling treatments. When the overwintering pupae were transferred at different times from natural temperatures to 25 °C, it was found that the earlier the transfer took place, the earlier the adults emerged when the time spent under natural conditions was included. However, cool temperatures before March showed an enhanced effect on diapause development at 20 °C, suggesting that the high diapause-terminating temperature can offset the effect of chilling on diapause development. The result of diapause termination under natural conditions suggests that the developmental threshold for post-diapause development in H. armigera should be around 17.5 °C.